FRI0621 Prevalence of different orbital anatomic structures affection in igg4-related ophthalmic disease: single center experience. (15th June 2017) - Vasilyev, V; Sokol, E; Safonova, T; Palshina, S; Kokosadze, N; Kovrigina, A
Abstract : Background: According to 2009 Japanese nationwide survey of IgG4-related disease (IgG4-RD), orbit is the leading site of affection [1]. However diagnostic criteria and nomenclature of IgG4-RD were developed a few years later [2, 3]. Objectives: To evaluate the peculiarities of clinical, laboratory, histological and immunohistochemical presentation of IgG4-related ophthalmic disease (IgG4-ROD). Methods: During 2004 – 2016, 82 patients were diagnosed with IgG4-RD 53 of whom had IgG4-ROD (men – 17, women - 36). The diagnoses of IgG4-RD and IgG4-ROD were established using comprehensive diagnostic criteria [2, 3]. In all patients full clinical, ophtalmological, dental and serological (rheumatoid factor, C-reactive protein, IgG, IgG4, IgM, IgA, ANA, anti-Ro/La, C3/C4 complement) examination was carried. In all cases diagnosis was verified pathomorphologicaly with immunohystochemical staining (anti-CD 138, CD 68, IgG, IgG4, κ-chain, λ-chain), but only in 43 patients the diagnosis of IgG4-RD was established on orbital tissues biopsy. Some patients at baseline were tested on B-cell clonality in tissue (on frozen tissue section or paraffin embedded) by PCR analysis of immunoglobulin V-D-J genes heavy chain rearrangements (FR1, FR2, FR3); monoclonal secretion was tested in serum protein electrophoresis. Results: 40 patients with IgG4-ROD had orbital lesions at the onset of the disease and 13 developed them after 2 - 9 years from the onset. The frequency of different orbital anatomic structures involvement see in table 1 . 15 (28%) patients had isolated orbital lesions while 38 (72%) had systemic IgG4-RD with simultaneous involvement of 2 - 7 other organs. 6 (14%) patients had unilateral orbital lesions. 23 (53%) patients with IgG4-ROD had associated IgG4-related sialoadenitis and nasal lesions. Most common pathomorphological features of IgG4-ROD see in table 2. The most common laboratory features of IgG4-ROD were elevation of: total serum IgG (44%), serum IgG4 (88%), serum IgE (61%) and monoclonal serum secretion (23%). Conclusions: In our cohort of IgG4-RD patients orbit is the leading site of the disease (64.5% of patients) and the disease onset (75% of patients). The majority of patients have bilateral orbital lesions (89%) and systemic course of the disease with other organ involvement (72%). Most often affected orbital anatomicstructures are lacrimal glands, extraocular muscles, retrobulbar infiltration with optic nerve thickening and fibroinflammatory lesions of eyelids. MALT-lymphoma of lacrimal gland and local AL-amyloidosis can complicate the long history of IgG4-ROD. Monoclonal serum secretion and B-cell clonality in the tissue in 23% of patients can potentially act as a background for lymphoma formation. References: Uchida K, Masamune A, Shimosegawa T et al. Prevalence of IgG4-related disease in Japan based on nationwide survey in 2009. IntJ.Rheumatol. 2012;2012:358371. Umehara H, Okazaki K, Masaki Y et al. A novel clinical entity, IgG4-related disease (IgG4RD): general concept and details. ModRheumatol. 2012; 22: 1–14. Stone JH, Khosroshahi A, Deshpande V et al. Recommendations for the Nomenclature of IgG4-Related Disease and Its Individual Organ System Manifestations. Arth.Rheum. 2012; 64:3061–3067. Disclosure of Interest: None declared